Approaches to Enhancing of Efficiency of Enterprises’ Bankruptcy Process - Tvaronavičienė, Manuela (Ekonomika, 2001)
1. Procedure of bankruptcy in Lithuania is ineffective, what stipulates quite high social costs of bankruptcy.2. Analysis of Lithuanian statistical data showed that significant part of insolvent enterprise (estimated 40%) is neither rehabilitated or reorganized nor liquidated-decision hasn’t been made at all. Such situation stipulates enhancing of labilities, what even more complicate liquidation process of insolvent enterprises.3. Problem of diagnostics of insolvency in Lithuania is quite urgent. No one from available criteria of insolvency could be treated as unconditionally acceptable for practical purposes. In the article suggested new accomplished insolvency criteria: balance value of assets reduced by value of pledged property compared to liabilities reduced by sum of credits received for the pledged property. Having in mind that formal criteria could cause procedure of bankruptcy even for firms, which suffer losses temporary, presented insolvency criterion should be tied up to one or several profitability indexes.4. Following change of sequence of fulfillment of financial claims would stipulate increase of efficiency of bankruptcy procedure: after meeting liabilities of collateral holders and employees, all left liabilities should be met proportionally. Government regulates business conditions, so should bear responsibility for impact of economical policy on financial results of business firm. Additionally the highest and the lowest limits of claims of other creditors should be set. That orientated partners of business firms to more extensive use of insurance from various risks and determined the smaller social costs of bankruptcy processes.